Factors Associated with Lifetime HIV Testing in Texas by Race/Ethnicity - Benavides Torres, Raquel Alicia; Wall, Kristin M.; Núñez Rocha, Georgina Mayela; Onofre Rodríguez, Dora Julia; Hopson, Laura (2012)
Introduction: In United States, roughly 1/5 of all HIV infected persons remain undiagnosed. Because HIV testing is critical to improve prevention efforts, more research is needed to understand the characteristics of individuals who get tested for HIV. Methods: This secondary analysis of the 2010 Texas Behavioral Risk Factor Surveillance System used data from 9,744 respondents between 18-64 years of age to evaluate the relationship between demographic characteristics (gender, race/ethnicity, age, area of residence, education, marital status, employment status, and income), healthcare characteristics (insurance status, having a primary provider, and access to healthcare), and HIV risk behaviors with ever having received an HIV test. Results: Significant associations between gender, age, area of residence, marital and employment status, and HIV risk behaviors and HIV testing in a Texas population by race/ethnicity were observed. Conclusions: These findings have important implications for future research into racial/ethnic disparities between lifetime HIV testing, and can help guide practitioners who work with populations at risk for HIV/AIDS in Texas.